STYLISTICS AND REGISTER AS CORE DETERMINANTS OF MEANING IN LANGUAGE AND TRANSLATION - Ismoilova Shaxrizoda Sanjar qizi; Zarnigor Hasanova Ixtiyor qizi (TADQIQOTLAR, 2026)
shaxrizoda909@gmail.com Abstract This article examines stylistics and register as fundamental determinants of meaning in language and translation, arguing that meaning is not an inherent property of words or grammatical structures but is constructed dynamically through contextual, functional, and stylistic choices. Drawing on functional linguistics and translation theory, the study demonstrates that stylistic variation encodes attitudes, emotions, and cultural values, while register organizes language according to situational parameters such as field, tenor, and mode. Through detailed theoretical discussion and illustrative examples, the paper shows that translation requires not only semantic equivalence but also the reconstruction of stylistic and register-based meaning. The article’s contribution lies in its systematic integration of stylistics and register into a unified framework for understanding meaning, highlighting their inseparability in both linguistic analysis and translation practice.